From Silesia to Catalonia and Back. An Alternative Continental Diagonal in the Late Middle Ages - Coulon, Damien (Sensus Historiae, 2024)
This article examines the a priori unexpected routes taken by some German merchants grouped in trading companies across Europe, from the Iberian Peninsula to Silesia,at the dawn of the fifteenth century. The analysis of these exchanges refers to the search for new markets on their part, leading to shifts in economic poles correlated with changes in trajectories on a European scale, as well as to decisive distributions of the different market networks; phenomena that refer to the logic of globalization that will lead to the “Great Discoveries.